2015
DOI: 10.15298/invertzool.12.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the buccal complex of Flabellina verrucosa (Gastropoda: Opisthobranchia)

Abstract: Buccal complex of Gastropoda is a complex structure consisting of the radula, odontophore and the buccal muscles. The general morphology and function of the buccal complex of Gastropoda was well-studied in several aspects. However, there are only a few integrated studies on both general and fine morphology, and the mechanism of feeding performed on opisthobranchs. Opisthobranchs' feeding mechanisms are very specific and diverse, because opisthobranch molluscs have highly-specified feeding preferences. Unlike t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The nudibranchs A. papillosa and C. verrucosa occur in the same shallow-water community, but C. verrucosa demonstrates non-specified feeding mode ( Mikhlina, Vortsepneva & Tzetlin, 2015 ), and its radula ( Figs. 2C , 2D ) does not take part in biting the prey.…”
Section: Discussionmentioning
confidence: 99%
“…The nudibranchs A. papillosa and C. verrucosa occur in the same shallow-water community, but C. verrucosa demonstrates non-specified feeding mode ( Mikhlina, Vortsepneva & Tzetlin, 2015 ), and its radula ( Figs. 2C , 2D ) does not take part in biting the prey.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has shown that the types and proportions of different sequestered NCs might vary greatly depending on the prey species chosen [22]. The radular morphology and the morphology of the buccal complex in nudibranchs is closely related to feeding mechanisms and dietary preferences [2,17,[31][32][33][34][35][36]. As a result, molluscs that have evolved different feeding preferences, and specific adaptations in buccal armature morphology may demonstrate several differences in their sequestered NC assemblage and cnidosac morphology.…”
Section: Introductionmentioning
confidence: 99%
“…2014; Mikhlina et al . 2015); or lateral paired serrated blades which are located by the sides of the radula (Gittenberger & Gittenberger 2005). Moreover, various taxa of modern gastropods have a dissimilar structure of the mandibles (Vortsepneva & Tzetlin 2014; Mikhlina et al .…”
mentioning
confidence: 99%
“…Moreover, various taxa of modern gastropods have a dissimilar structure of the mandibles (Vortsepneva & Tzetlin 2014; Mikhlina et al . 2015). Their jaws vary not only in shape and location, but also in mechanism of formation during ontogenesis, which suggests that the jaw‐like structures had appeared in different evolutionary lines of gastropods independently (Vortsepneva & Tzetlin 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation